1999
DOI: 10.1080/104732299303386
|View full text |Cite
|
Sign up to set email alerts
|

Working Conditions and Health in Hairdressing Salons

Abstract: The purpose of the study was to assess the working conditions in hairdressing salons and the influence of work factors on the workers' health. Twenty randomly sampled hairdressing salons in the Helsinki, Finland, metropolitan area were selected for the study. The study was performed during winter 1994-1995; it included a survey of the hairdressing chemicals in use, the measurement of physical and chemical working conditions, and a self-administered questionnaire of the work environment and health of the worker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 10 publications
4
46
1
Order By: Relevance
“…Similar findings have been demonstrated in a Finnish study (Leino et al 1999). Limit values for carbon dioxide are much higher than the registered values in the salons, (5.000 ppm, OSHA) indicating that these levels present no health hazard (U.S. Environmental Protection Agency, Office of Air and Radiation 1989).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Similar findings have been demonstrated in a Finnish study (Leino et al 1999). Limit values for carbon dioxide are much higher than the registered values in the salons, (5.000 ppm, OSHA) indicating that these levels present no health hazard (U.S. Environmental Protection Agency, Office of Air and Radiation 1989).…”
Section: Discussionsupporting
confidence: 75%
“…Although several investigations describe health problems among hairdressers that might be related to their occupation, and possibly to chemical exposures ( Van der Wal et al 1997;Leino et al 1998;Gago-Dominguez et al 2001;Hollund et al 2001;Kersemaekers et al 1997;Albin et al 2002) very few studies are published showing chemical exposure levels in hairdressing salons (Muiswinkel et al 1997;Hollund and Moen 1998;Leino et al 1999;Labreche et al 2003;Mounier-Geyssant et al 2006). They focus on the determination of certain chemicals, finding different exposure profiles and point out the importance of the local exhaust ventilation.…”
Section: Introductionmentioning
confidence: 96%
“…However, the age trend was not statistically significant. Several studies (8,14,(25)(26)(27)(28) have found declining IgE levels with increasing age. We have previously shown (3) that hairdressers older than 40 years of age report a significantly higher prevalence of airway symptoms, and this trend can have parallel explanations to the IgE change related to age.…”
Section: Discussionmentioning
confidence: 99%
“…Today, the exposure to some of the most hazardous chemicals has been substantially reduced and new products that are less irritative and dusty have been introduced. Hairdressers are exposed to many different chemicals, but at low levels when compared with the Norwegian threshold limit values (6,28). The exposure time is usually short, only a few minutes for each customer.…”
Section: Discussionmentioning
confidence: 99%
“…Presumably the levels of exposure to chemical agents, for instance with endocrine-disrupting properties, in hairdressing salons are of insufficient magnitude to interfere adversely with the development of the male reproductive tract. The exposure level has plausibly been reduced within the last decades due to a ban of some hazardous chemicals and increased attention to working conditions (eg, in relation to ventilation) (2,34). It might thus be expected that children of hairdressers born in the 1980s or 1990s had a higher exposure and thus possibly a higher relative risk than children born in the 2000s.…”
Section: Jørgensen Et Almentioning
confidence: 99%